2022
DOI: 10.1002/marc.202100862
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Fibers and Matrices in Natural Fiber Reinforced Polymer Composites: A Comprehensive Review

Abstract: Application of natural fiber-polymer composites (NFPCs) in different industrial applications provides competitive edge due to their lightweight, higher specific mechanical properties than glass fibers, sustainability, and lower cost involved in production. There are certain challenges associated with natural fibers and their reinforcement in composites such as poor bonding between the fibers and matrix due to their contradictory nature of characteristics, moisture absorption, lower thermal properties, and poor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(29 citation statements)
references
References 399 publications
0
18
0
Order By: Relevance
“…In the point of biodegradability, the composite CFFC is suitable for products development with a partially environmentally friendly nature. [61][62][63][64][65]…”
Section: Tensile Propertiesmentioning
confidence: 99%
“…In the point of biodegradability, the composite CFFC is suitable for products development with a partially environmentally friendly nature. [61][62][63][64][65]…”
Section: Tensile Propertiesmentioning
confidence: 99%
“…ArunRamnath in his research investigations reviewed and experimentally investigated the machining performance of various composite materials for determination of suitable optimization technique and ideal machining parameter combinations with regard to the selection of ideal machining parameters in end milling epoxy granite composites. [42][43][44][45][46][47][48][49][50][51] With a similar research methodology, the results of static, dynamic and thermal characteristics of research investigations of 70 different machine tool structures are identified and summarized and further the design methodologies employed are analyzed with the objective of enhanced performance and functionality of machine tool structures. This review work performed provides a clear ideology on machine tool structures and aids researchers, scientists and metallurgists in development of machine tool structures by epoxy granite composites and other polymer concrete reinforced composites with the objective of minimization of thermal errors without any trade-off among static and dynamic properties.…”
Section: Introduction and Present Scenariomentioning
confidence: 99%
“…They have appropriate mechanical properties for a wide range of applications such as excellent acoustic, mechanical, and thermal insulation properties. The use of plant‐based biodegradable “lignocellulosic” materials as fillers makes the product environmentally safe, and they are believed to be “environmentally superior” to composites made using glass fibers 19 …”
Section: Introductionmentioning
confidence: 99%
“…The use of plant-based biodegradable "lignocellulosic" materials as fillers makes the product environmentally safe, and they are believed to be "environmentally superior" to composites made using glass fibers. 19 Despite their numerous advantages, natural fibers are rarely used as thermoset reinforcements. Green composites based on biodegradable polymers and plant fibers appear to have some potential.…”
Section: Introductionmentioning
confidence: 99%